Attractiveness of polish labour market in relation to foreign direct investments - Rezmer, Aleksander (Torun International Studies, 2010)
<!–[if gte mso 9]> <![endif]–><span style="font-size: 11.0pt; line-height: 115%; font-family: ’Calibri’,’sans-serif’; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Attractiveness of polish labour market in relation to foreign direct investments The aim of this study is to analyse attractiveness of Polish Labour Market for foreign investors, who seek new localisations for their investments. In the first part of the study the general attractiveness of Poland as a host country of foreign direct investments is taken under general analysis. The second part of the article consists of the theoretical background of the study, which is the J.Dunning’s theory of International Production. The next three parts of the article are devoted to deeper analysis of polish labour market as a variable of three features: workforce availability, labour costs and education. The analysis is conducted both on local and international level. The conclusion of the article is that besides the recent, unfavourable changes, polish labour market still remains attractive in relation to foreign direct investment.<!–[if gte mso 9]> Normal 0 21 false false false PL X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–><!–[if gte mso 9]> <![endif]–><span style="font-size: 11.0pt; line-height: 115%; font-family: ’Calibri’,’sans-serif’; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Attractiveness of polish labour market in relation to foreign direct investments The aim of this study is to analyse attractiveness of Polish Labour Market for foreign investors, who seek new localisations for their investments. In the first part of the study the general attractiveness of Poland as a host country of foreign direct investments is taken under general analysis. The second part of the article consists of the theoretical background of the study, which is the J.Dunning’s theory of International Production. The next three parts of the article are devoted to deeper analysis of polish labour market as a variable of three features: workforce availability, labour costs and education. The analysis is conducted both on local and international level. The conclusion of the article is that besides the recent, unfavourable changes, polish labour market still remains attractive in relation to foreign direct investment.<!–[if gte mso 9]> Normal 0 21 false false false PL X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>